2018
DOI: 10.1042/bsr20180453
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of microRNAs in bone remodeling and its therapeutic implications for osteoporosis

Abstract: Osteoporosis, a common and multifactorial disease, is influenced by genetic factors and environments. However, the pathogenesis of osteoporosis has not been fully elucidated yet. Recently, emerging evidence suggests that epigenetic modifications may be the underlying mechanisms that link genetic and environmental factors with increased risks of osteoporosis and bone fracture. MicroRNA (miRNA), a major category of small noncoding RNA with 20–22 bases in length, is recognized as one important epigenetic modifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 72 publications
0
66
0
Order By: Relevance
“…Recent evidence indicates that, among the mechanisms by which naturally occurring compounds, such as resveratrol and anthocyanin, impact bone cell activities, the bone epigenome exerts a fundamental role [19]. The epigenetic regulation of osteoblast activity refers to the mechanisms that impact gene expressions such as post-translational histone modifications, miRNA-mediated post-transcriptional regulation, and DNA methylation [41,42]. In the present study, we examined the possible epigenetic mechanisms by which δTT exerts its positive effects on MC3T3-E1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence indicates that, among the mechanisms by which naturally occurring compounds, such as resveratrol and anthocyanin, impact bone cell activities, the bone epigenome exerts a fundamental role [19]. The epigenetic regulation of osteoblast activity refers to the mechanisms that impact gene expressions such as post-translational histone modifications, miRNA-mediated post-transcriptional regulation, and DNA methylation [41,42]. In the present study, we examined the possible epigenetic mechanisms by which δTT exerts its positive effects on MC3T3-E1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Another class of molecules useful for conjugation with biomimetic materials is represented by miRNAs because of their known involvement in different diseases (for example, osteoporosis and osteoarthritis, for what pertains to bone) and of the wide availability of synthetic mimics or inhibitors [ 120 , 121 ]. Also, in this case, scaffold-based delivery systems, in which these small compounds are encapsulated or immobilized through different procedures, may result in sustained local concentration of the active molecule [ 122 , 123 , 124 ].…”
Section: Msc-seeded Scaffolds As a Source Of Soluble Factorsmentioning
confidence: 99%
“…miRNA is a type of endogenous small non‐coding RNA that often functioned through post‐transcriptional repression . Several miRNAs have been implicated in bone metabolism and osteogenic regulation . Our previous study has confirmed miR‐375 as a positive regulator in the osteogenic differentiation of MSCs, and overexpression of miR‐375 significantly enhanced the alkaline phosphatase (ALP) activity and calcium deposition in hASCs, suggesting that miR‐375‐mediated therapy might be a viable approach to repair bone defects .…”
Section: Introductionmentioning
confidence: 98%